用于功率超声磨削声学系统的阶梯型变幅杆节点位置研究 - 阳培; 赵波 (Jixie chuandong)
Through theoretical derivation and finite element simulation,the difference between the actual node position and the theoretical node position of the stepped horn is found.At the same time,the lateral deformation of material will occur when the ultrasonic wave transmit in the stepped horn is presented.That is to say,the longitudinal elastic deformation will induce to generate the lateral deformation of material because Poisson ratio exist.The vibration character of the stepped horn is analyzed.That the node disk can be reduced by moving the node position to the thin side is pointed out.Through the experiment about the node position of the horn,the results show that above-mentioned conclusion is correct.